Single-Site Robotic Radical Hysterectomy and Sentinel Lymphnode Biopsy in Cervical Cancer: A Case Report - Silva e Silva, Alexandre; Fernandes, Rodrigo Pinto; Araujo, Marcia Pereira de; Carvalho, João Paulo Mancusi de; Carvalho, Filomena Marino; Favero, Giovani Mastrantônio; Carvalho, Jesus Paula (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Robotic surgeries for cervical cancer have several advantages compared with laparotomic or laparoscopic surgeries. Robotic single-site surgery has many advantages compared with the multiport approach, but its safety and feasibility are not established in radical oncologic surgeries. We report a case of a Federation of Gynecology and Obstetrics (FIGO) stage IB1 cervical carcinoma whose radical hysterectomy, sentinel lymph node mapping, and lymph node dissection were entirely performed by robotic single-site approach. The patient recovered very well, and was discharged from the hospital within 24 hours.
Keywords: hysterectomy; cervical cancer; single-site robotic laparoscopy; lymphadenectomy; robotics; laparoendoscopic single-site surgery